El uso de cámaras ocultas, por parte de medios de comunicación televisivos de la ciudad de Quito, como recurso ético en el periodismo de investigación y su incidencia en el derecho a informar versus el derecho a la privacidad, periodo octubre 2012-octubre 2013. Propuesta alternativa - Cuenca Ludeña, Monica Vanesa (2014)
This paper focuses on a study of how social media television Quito perform investigative journalism, particularly in designing an ethical if the use of hidden cameras and how this affects the right to informed of the right to privacy , according to the scenario in which the media operate with the purpose of informing. The information obtained from the field investigation reveals that Quito television media used hidden cameras to investigative journalism, despite being an unethical action; however do not pay the most attention, because all they want is to get information. To better explain how this problem is turned to the use of scientific methods, inductive, deductive, and techniques such as surveys and interviews, which allowed resources to better clarify the phenomenon in question. Also, with all the baggage of criteria and thoughts given by the respondents , were obtained to verify the objectives outlined in the research project , in addition to the testing of the hypothesis , as a result of the field study , this explanation is given in a clear results and their discussion by presenting statistical tables and charts , they are accompanied by their quantitative and qualitative analysis , noting that social media investigative journalism Quito performed through the use of hidden cameras ; since it is necessary to design an alternative proposal so that it can perform investigative journalism, without resorting to illegal means. Finally an alternative arises requiring that social media television, investigative journalism made without the use of hidden cameras, because it constitutes an unethical action. For this last statement is realized , it will require the help and contribution of managers social media , in order to improve data collection processes in an honest , ethical and objective. Keywords: Hidden Camera, Television, Ethics, Journalism Research, Information, Privacy, Right.